2019
DOI: 10.1111/apm.12941
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity and apoptotic action of coelomic fluid from the earthworm Dendrobaena veneta against A549 human lung cancer cells

Abstract: It is known that earthworm coelomic fluid (CF) can affect not only cancer but also normal cells. The study demonstrated that the CF of the earthworm Dendrobaena veneta exhibited cytotoxicity against A549 lung cancer cells but did not toward the bronchial epithelial cell line BEAS‐2B. The selective effect on the tumor cells was achieved after a short‐term CF heat pre‐treatment at 70 °C. The cytotoxic effect of the CF was time‐ and concentration‐dependent. The CF noticeably decreased the viability and affected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 32 publications
(38 reference statements)
2
26
4
Order By: Relevance
“…There is ample evidence proving that, in higher eukaryotes, damaged mitochondrial compartments in a susceptible cell can inappropriately trigger cell death through the untimely loss of cytochrome c, i.e., a positive effector of apoptosis 75 77 . This fact may explain the confirmed activity of AAF on lung cancer cells A549 31 and human colon adenocarcinoma cells 32 .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…There is ample evidence proving that, in higher eukaryotes, damaged mitochondrial compartments in a susceptible cell can inappropriately trigger cell death through the untimely loss of cytochrome c, i.e., a positive effector of apoptosis 75 77 . This fact may explain the confirmed activity of AAF on lung cancer cells A549 31 and human colon adenocarcinoma cells 32 .…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, the study did not show any undesirable effects of cytotoxicity and endotoxicity to normal human fibroblasts 30 . The fraction exhibits antitumor activity against A549 lung cancer 31 and human colon adenocarcinoma cells 32 . The properties of the active fraction make it a promising potential agent for the treatment of candidiasis; therefore, its mechanism of action should be thoroughly analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…A particularly important step was to deprive the fluid from cytotoxicity to normal cells while maintaining its high activity against tumor cells. These processes were described in the publication describing the action of fractions from coelomic fluid on A549 lung cancer cells 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Earthworm preparations have documented antibacterial and antifungal properties 20 , 21 , 24 28 . Current research has demonstrated that coelomic fluid has anticancer activity against HeLa, A549, Pa17, PC-12, or Hep-2 cancer cell lines 20 , 26 , 29 . A mechanism of the coelomic fluid action against cancer cells based on limitation of glucose uptake by cells has been proposed 20 .…”
Section: Introductionmentioning
confidence: 99%
“…C. albicans is the most common fungus causing infection in humans. AAF has been identified as a protein-carbohydrate fraction from D. veneta earthworm CF with antifungal activity against C. albicans, C. krusei strains 24 , and A549 lung cancer cells with approximately 90% cytotoxicity in vitro 34 . It is important that AAF showed no cytotoxicity effect on normal bronchial epithelium BEAS 2B cells.…”
Section: Discussionmentioning
confidence: 99%